Low leakage decoder using dual-threshold technique for static random-access memory applications - R. Krishna; Punithavathi Duraiswamy (Institute of Advanced Engineering and Science, 2023)
Decoders are one of the significant peripheral components of static random-access memory (SRAM). As the CMOS technology moves towards nano scale regime, the leakage power starts dominating dynamic power. In this paper, we propose decoders using NAND logic in 32 nm CMOS technology. Leakage power is reduced by employing dual-threshold technique. Dual thresholding is a technique that uses transistors of two different threshold voltages. The technique is implemented in simulation by two methods; first method uses transistors with different threshold voltage and the second method uses substrate biasing to vary the threshold voltage. Row and column decoders are designed and simulated in H-Spice. The leakage power is calculated and compared for both the methods. The NAND gate implemented by Method-1 and Method-2 provides a maximum leakage power savings of 87.67% and 90.81% respectively. The maximum leakage power savings of 96.76% and 98.74% is reported for the row decoder implemented by Method-1 and Method-2 respectively. Similarly, Method-1 gives maximum leakage power savings of 97.09% and Method-2 gives a savings of 99.11% for column decoder. The difference in leakage power savings of Method-1 and Method-at same threshold voltage is 3.14%, 1.98%, and 2.02% for NAND gate, row decoder and column decoder respectively.